2018
DOI: 10.3390/s18010108
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Multi-Agent Systems and Wireless Sensor Networks for the Monitoring of Cattle

Abstract: Precision breeding techniques have been widely used to optimize expenses and increase livestock yields. Notwithstanding, the joint use of heterogeneous sensors and artificial intelligence techniques for the simultaneous analysis or detection of different problems that cattle may present has not been addressed. This study arises from the necessity to obtain a technological tool that faces this state of the art limitation. As novelty, this work presents a multi-agent architecture based on virtual organizations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 40 publications
(44 reference statements)
0
25
0
Order By: Relevance
“…Besides, several new techniques and application have been introduced and patented to improve the traditional agriculture practices. However, experts mainly focused and monitor the climatic condition, soil properties, water quality, plant development, livestock management, and fertilizer application, pesticide application, and illumination control through various intelligent techniques [26][27][28][29][30][31][32]. Meanwhile, it could be concluded that traditional agricultural logistics is improved and upgraded by introducing and implementing the several modern technologies and techniques in agriculture domains [33].…”
Section: Related Workmentioning
confidence: 99%
“…Besides, several new techniques and application have been introduced and patented to improve the traditional agriculture practices. However, experts mainly focused and monitor the climatic condition, soil properties, water quality, plant development, livestock management, and fertilizer application, pesticide application, and illumination control through various intelligent techniques [26][27][28][29][30][31][32]. Meanwhile, it could be concluded that traditional agricultural logistics is improved and upgraded by introducing and implementing the several modern technologies and techniques in agriculture domains [33].…”
Section: Related Workmentioning
confidence: 99%
“…Virtual organization of agents have evolved from traditional MAS architectures, they allow for the organization of groups according to their tasks within the system [ 38 ]. They also allow for solving complex sub-problems (like sensor management, data collection, information analysis or decision making [ 39 ]).…”
Section: Related Workmentioning
confidence: 99%
“…Multi-agent systems are computational distributed systems with high capacities for learning and adaptation and can be very appropriate to design pervasive systems [10]. Multi-agent systems have been successfully used to develop pervasive systems in different scenarios [7,11,12] and can contribute to improving the labour and social integration of disabled people [8]. Multi-agent systems not only provide distributed communication and computation capacities, but also reasoning and adaptation abilities, which allow us to design intelligent adaptive environments in a simple and flexible way, for example, to help visually disabled people in common tasks such as recognizing objects like coins in different situations of their daily life.…”
Section: Introductionmentioning
confidence: 99%